The Breast Cancer Susceptibility Gene BRCA1 Regulates Progesterone Receptor Signaling in Mammary Epithelial Cells - Ma, Yongxian (2005)
The progesterone receptor (PR) plays roles in normal mammary development and breast cancer formation, where it may exert both stimulatory and inhibitory actions. Previously, the breast cancer susceptibility gene product BRCA1 was found to interact with and inhibit the transcriptional activity of estrogen receptor-α. In this study, we found that exogenous wild-type BRCA1 inhibited the activity of the PR in transient transfection assays utilizing a mouse mammary tumor virus-Luc reporter. Wild-type BRCA1 inhibited the activity of endogenous PR in human breast cancer cells (T47D and MCF-7) and inhibited the activity of exogenous PR-A, PR-B, and [PR-A plus PR-B] isoforms. On the other hand, knockdown of endogenous BRCA1 using small interfering RNA enhanced the progesterone-stimulated activity of the PR by about 4-fold. We documented an in vivo association of the endogenous BRCA1 with PR isoforms A and B and a direct in vitro interaction between BRCA1 and PR, which was partially mapped. Whereas down-regulation of the coactivator p300 contributes to the BRCA1-mediated repression of estrogen receptor-α, this mechanism does not contribute to inhibition of PR activity, because exogenous p300 did not rescue the BRCA1 repression of PR activity. The BRCA1-PR interaction has functional consequences. Thus, we showed that BRCA1 inhibits the expression of various endogenous progesterone-responsive genes and inhibits progesterone-stimulated proliferation of T47D cells. Finally, exogenous progesterone caused an exaggerated proliferative response in the mammary glands of mice harboring a mammary-targeted conditional deletion of the full-length isoform of Brca1. These findings suggest that BRCA1 regulates the activity of progesterone, a major hormone of pregnancy that may also participate in mammary carcinogenesis.